Database watermarking, a technological protective measure: Perspective, security analysis and future directions. (December 2017) - Khanduja, Vidhi
Abstract: Digital Databases dynamically generates a major proportion of the internet content. The databases are created, stored and accessed digitally and transmitted through computer networks. This has grown the potential, sizes and performance of databases in exponential magnitudes. Thus, the need to protect digital databases arises due to the increased vulnerability to copyright and piracy threats originating from the Internet. Both legal and technological measures must be utilized in a synergetic manner to ensure an adequate level of protection. TPMs backed by legal anti-circumvention measures offer a cost-effective solution to database protection. We provide the current state-of-art and analyses of the arena of digital database protection from a combined legal and technical perspective. Our work is more focused on security analysis of the work done so far and provides readers with detailed discussion on the future directions in the domain of digital watermarking of databases.